The Effect of Interval Training on the Performance of Tennis Athletes: Pengaruh Latihan Interval Terhadap Kinerja Atlet Tenis Lapangan - Dwi Putri, Adinda; Fitri, Soleha; Dirwansyah, Dino; Prawibowo, Muhammad; Kurnia, Jundri (Badnur Medisa Group, 2025)
This study aims to determine the effect of interval training on the performance of tennis athletes. Interval training is a training method that combines periods of intense activity with periods of rest or light activity, believed to be effective in improving athletes' physical capacity and performance, particularly in intermittent sports such as tennis.The research method used was a quantitative method with an experimental design. The subjects in this study were tennis athletes from [specify club/school/institution], who were divided into two groups: an experimental group given interval training, and a control group receiving conventional training. Data was collected by measuring various aspects of athlete performance, such as endurance, speed, agility, and shot accuracy, both before and after the treatment.The results of the data analysis showed a significant increase in performance in the interval training group compared to the control group. These findings indicate that interval training has a positive effect on tennis athlete performance, particularly in improving physical ability and endurance.Therefore, interval training can be recommended as part of a regular training program for tennis athletes to support overall performance improvement.